Correlation between hepatic morphology and immunoglobulins and antibodies to Escherichia coli in cirrhosis. Issue 1 (January 1977) - Prytz, H; Bjorneboe, M; Christoffersen, P; Poulsen, H; Orskov, F
Abstract : Increased antibody production and hypergammaglobulinaemia in cirrhosis are probably to a large extent due to decreased hepatic extraction of antigens. The deceased extraction is presumably related to changed microcirculation caused by damaged anatomical structure of the liver. It is therefore to be expected that immunoglobulin and antibody levels in serum in cirrhotic patients are related to the degree of certain morphological changes of the liver. This hypothesis has been tested. In 50 patients with cirrhosis, 28 alcoholics and 22 non-alcoholics, the degree of architectural destruction, the degree of fibrosis, the degree of fatty infiltration, and the degree of "activity" were compared with immunoglobulins G, A, and M and E. coli O antibody levels. The comparison was carried out within each of the aetiological groups. Identical relationships were found in both groups. Patients with completely destroyed lobular architecture had higher levels of E. coli O antibodies than patients with partly destroyed architecture. Patients with severe fibrosis had higher IgA and E. coli O antibody levels than patients with moderate or slight fibrosis. Patients with moderate and severe steatosis and patients with no or slight steatosis had the same immunoglobulin and E. coli O antibody levels. Patients with active cirrhosis had higher IgG levels than patients with inactive cirrhosis. When architectural destruction and fibrosis were combined significantly higher IgG, IgA, IgM, and E. coli antibodies were found in the group with the most severe changes. These findings support the hypothesis that immunoglobulin and antibody levels are related to the degree of morphological changes in the liver--namely, destruction of lobular architecture, fibrosis, and "activity".